NEW MODEL FOR THE EARLY CRETACEOUS DEVELOPMENT OF SW JAPAN BASED ON BASIC ROCKS OF THE CHIEHIBU COMPOSITE TERRANE - Kato K.; Saka Y. (My University, 2006)
The Kurosegawa Terrane in SW Japan is a fault zone that divides the Chichibu Composite Terrane into the Northern Chichibu and Southern Chichibu Terranes. It contains exotic tectonic blocks including granitoids, variously metamorphosed rocks and Siluro-Devonian deposits together with tectonic slices of the Jurassic-Early Cretaceous accretionary complexes. It is also intimately associated with Cretaceous forearc basin deposits. Understanding of the Kurosegawa Terrane is regarded as a key to clarify the Mesozoic geotectonic history of the western circum-Pacific erogenic belts. Detailed studies of the geochemistry of basic rocks of the Chichibu Composite Terrane in eastern Kii Peninsula revealed that HIIVIU basalts are included in basic rocks. The presence of HIMU basalts provides further evidence for the existence of the Kurosegawa Terrane in this area and supports our model on the tectonic evolution of the Kurosegawa Terrane as a transform fault zone formed due to oceanic ridge subduction in the late Early Cretaceous. This model can comprehensively describe not only the features of the Kurosegawa Terrane but also the coeval key situations of the western circum-Pacific erogenic belts.
Keywords: ACCRETIONARY COMPLEX; HIMU BASALT; KUROSEGAWA TERRANE; SOUTHWEST JAPAN; TRANSFORM FAULT; Cretaceous; Jurassic; Devonian; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Jurassic; Мезозой::Юрская; Paleozoic::Devonian; Палеозой::Девонская